AGENCY IN THE ONLINE MATCHMAKING PLATFORM: Study of Rumah Taaruf myQuran and Mawaddah Indonesia - Nugroho, Ishak Tri (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
The emergence of the online ta'aruf matchmaking platform represents a shift in the community's religious practice from offline to online media. The matchmaking platform’s use of internet technology is a unique selling point, as it attracts a large number of members. Apart from the religious messages propagated by each platform, the emergence of the online taaruf matchmaking media is undoubtedly sustained by the agencies involved in order to attract its members. The purpose of this article is to discuss the role of agents in two online matchmaking platforms: Rumah Taaruf myQuran and Mawaddah Indonesia. This research employs an agency theory framework. Based on the data gathered, this study concludes that the success of these two platforms is a reflection of the performance of the numerous agents involved. These agents are not gender-specific, but rather multi-agency.Munculnya biro jodoh taaruf online merupakan sebuah perubahan sosial dari praktik keagamaan masyarakat dari model offline beralih menjadi online. Pemanfaatan teknologi internet oleh para biro jodoh menjadikan daya tarik tersendiri sehingga banyak yang menggunakan jasanya. Selain bersandar kepada pesan-pesan keagamaan yang dikampanyekan oleh masing-masing, kemunculan biro jodoh taaruf online tersebut tentu ditopang oleh para agensi yang terlibat sehingga sukses menjaring para pencari jodoh. Tulisan ini mengulas tentang bagaimana agen berperan dalam platform perjodohan online: Rumah Taaruf myQuran dan Mawaddah Indonesia. Penelitian ini berda pada pendekatan teori agensi. Berdasarkan data yang didapatkan, penelitian ini berkesimpulan bahwa kesuksesan kedua platform ini merupakan representasi dari kinerja banyak agen yang terlibat. Para agen ini tidak dipecah berdasarkkan gender melainkan multiagensi.